Analisis Pengaruh Penghindaran Pajak dan Profitabilitas Terhadap Nilai Perusahaan Melalui Tata Kelola Perusahaan pada Perusahaan Manufaktur di Bursa Efek Indonesia - Santosa, Herlambang Pudjo (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This purpose of this research s to determine and prove the effect of Tax Avoidance and profitability with the moderating variable Corporate Governance on company value. The population in this study are manufacturing companies listed on the ndonesian Stock Exchange. A sample of 20 companies was obtained using a purposive sampling technique with 100 observation data. WrapPLS 7.0 for Windows was used as a tool in the Structural Equation Model (SEM) analysis method n this research. The results obtained in this research state that Tax Avoidance has no effect on company value, while profitability has a positive effect on company value. Good corporate governance cannot have a moderating effect on the relationship between Tax Avoidance and company value, but Corporate Governance has a moderating effect and strengthens the relationship between profitability and company value.